2008
DOI: 10.1893/0005-3155(2008)79[103:peotae]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Research Article: Pharmacological effects of the aqueous extract of Caulophyllum thalictroides (blue cohosh) on isolated Mus musculus uteri

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…12 There are several in vitro studies, which have demonstrated strong uterine contractile responses to herbal preparations when employing isolated issues in organ baths. For example, individual aqueous extracts from the roots and rhizomes of blue cohosh Caullophylum thalactroides 16 , red raspberry leaves Rubus ideaus 17 , castor beans Ricinus communis 18 , evening primrose seeds Oenothera biennis 19 , and clary sage Salvia sclarea 20 have all been shown to produce strong contractile responses in isolated mouse uterine tissues similar to those evoked following an application of 10 -5 M oxytocin. In all cases, the uterine contractile responses to these treatments were statistically greater than those of the controls (p < 0.05), or the "0" treatment, which is the endogenous, spontaneous rhythmicity of the uterine tissue itself when under a given amount of tension.…”
Section: Introductionmentioning
confidence: 99%
“…12 There are several in vitro studies, which have demonstrated strong uterine contractile responses to herbal preparations when employing isolated issues in organ baths. For example, individual aqueous extracts from the roots and rhizomes of blue cohosh Caullophylum thalactroides 16 , red raspberry leaves Rubus ideaus 17 , castor beans Ricinus communis 18 , evening primrose seeds Oenothera biennis 19 , and clary sage Salvia sclarea 20 have all been shown to produce strong contractile responses in isolated mouse uterine tissues similar to those evoked following an application of 10 -5 M oxytocin. In all cases, the uterine contractile responses to these treatments were statistically greater than those of the controls (p < 0.05), or the "0" treatment, which is the endogenous, spontaneous rhythmicity of the uterine tissue itself when under a given amount of tension.…”
Section: Introductionmentioning
confidence: 99%